2014
DOI: 10.3389/fncel.2014.00144
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 modulation of CXCR4 and CXCR7 activity in human glioblastoma stem-like cells and regulation of the tumor microenvironment

Abstract: Chemokines are crucial autocrine and paracrine players in tumor development. In particular, CXCL12, through its receptors CXCR4 and CXCR7, affects tumor progression by controlling cancer cell survival, proliferation and migration, and, indirectly, via angiogenesis or recruiting immune cells. Glioblastoma (GBM) is the most prevalent primary malignant brain tumor in adults and despite current multimodal therapies it remains almost incurable. The aggressive and recurrent phenotype of GBM is ascribed to high growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 194 publications
(274 reference statements)
1
130
0
1
Order By: Relevance
“…In particular, it is believed that CSCs are especially efficient in modulating their microenvironment. 38,39 One specific way that CSCs may be involved in interacting with their microenvironment is during metastasis. 40 It has been suggested that they are particularly endowed with the capability to utilize the EMT mechanism.…”
Section: Cancer Stem Cells (Cscs) and Their Microenvironmentmentioning
confidence: 99%
“…In particular, it is believed that CSCs are especially efficient in modulating their microenvironment. 38,39 One specific way that CSCs may be involved in interacting with their microenvironment is during metastasis. 40 It has been suggested that they are particularly endowed with the capability to utilize the EMT mechanism.…”
Section: Cancer Stem Cells (Cscs) and Their Microenvironmentmentioning
confidence: 99%
“…Several studies have reported that stem cells mobilization mechanism may involve cytokines, chemokines, and growth factors released at the injured site and hypoxia environment [20]. Stromal cell-derived factor 1 (SDF-1), which is a strong chemoattractant, is widely expressed by a variety of tissues such as the bone marrow, heart, liver, lung, lymph nodes, kidney, and brain [21]. SDF-1 and its receptor CXCR4 play vital roles in the homing of stem cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of CSCs within tumors, together with the active pathological role currently recognized for the tumor microenvironment that influences acquired resistance, immune evasion and metastization [20,21], further favors the search for a combination of repurposed drugs against the whole tumor system, likely acting on intracellular mechanisms that differ from those targeted by standard anticancer agents [22].…”
Section: Why Reposition Existing Noncancer Drugs For New Uses In Oncomentioning
confidence: 99%